Melioidosis: a major cause of community-acquired septicemia in northeastern Thailand. - Chaowagul, W; White, N; Dance, D; Wattanagoon, Y; Naigowit, P; Davis, T; Looareesuwan, S; Pitakwatchara, N (1989)
In a prospective study of all patients with Pseudomonas pseudomallei infections admitted to a large provincial hospital in northeastern Thailand, 63 cases of septicemic melioidosis and 206 patients with other community-acquired septicemias were documented during a 1-y period. Apart from P. pseudomallei, the spectrum of bacteria isolated from blood cultures and the overall mortality (32%) were similar to those previously reported elsewhere. Death from septicemia was associated with failure to develop a leukocytosis or pyrexia over 38 degrees C, azotemia, hypoglycemia, and jaundice. Septicemic melioidosis presented mainly in the rainy season, occurred predominantly in rice farmers or their families, and was significantly associated with preexisting diabetes mellitus or renal failure (P = .03). Blood-borne pneumonia and visceral abscesses were common and the mortality was high (68%; P less than .001). The response to appropriate treatment was slow (median fever clearance time 5.5 d) and the median duration of hospital stay was 4 w. Septicemic melioidosis is a major cause of morbidity and mortality in northeast Thailand.